Bioinformatics analysis to explore biomarkers and mechanisms of action associated with endoplasmic reticulum stress and ferroptosis in Parkinson’s disease - Hao Wang; Lijuan Feng; Limeng He; Nan Liu; Yan Wan; Wei Zhang (PLoS ONE, 2025)
Objective It has been demonstrated that Parkinson’s disease (PD) is closely associated with endoplasmic reticulum stress (ERS) and ferroptosis. However, the specific mechanisms underlying these associations remain unclear. Consequently, this study investigated the mechanisms connecting these factors and explored potential biomarkers for PD. Methods Data for PD and ERS, as well as information on ferroptosis, were sourced from public databases and relevant literature. Candidate genes were identified through differential expression analysis and weighted gene co-expression network analysis. Further investigations included functional enrichment analysis, the construction of a protein-protein interaction (PPI) network, and the examination of related genes. Subsequently, biomarkers were validated using the least absolute shrinkage and selection operator regression algorithm. Additionally, correlations among biomarkers, gene set enrichment analysis, chromosomal and subcellular localization, immune cell infiltration, regulatory mechanisms, and drug predictions were conducted. Results Initially, seven candidate genes were identified, predominantly associated with type II diabetes mellitus. Furthermore, five interacting associations within the PPI network and twenty related genes were identified, primarily engaged in the physical interactions pathway. Subsequently, three biomarkers were screened: N-myc downstream-regulated gene 1 (NDRG1), dihydrolipoamide dehydrogenase (DLD), and cold-inducible RNA-binding protein (CIRBP). A detailed analysis revealed a positive correlation between CIRBP and DLD, while NDRG1 exhibited a negative correlation with DLD; all three biomarkers were chiefly enriched in the oxidative phosphorylation pathway and PD. NDRG1 is located on chromosome 8, DLD on chromosome 7, and CIRBP on chromosome 19, with all three primarily localized in the nucleus. A total of 31 differential immune cells were identified between the disease and control groups, with neurons representing the highest proportion and the most significant negative correlation observed between DLD and pro B-cells. The interactions involving NORAD-hsa-miR-1277-5p-DLD, NEAT1-hsa-miR-128-3p-CIRBP, and XIST-hsa-miR-3173-5p-NDRG1 were found to be pivotal. Additionally, these biomarkers were regulated by 15 common transcription factors. Finally, nicotinamide adenine dinucleotide, pyruvic acid, nitric oxide, and phosphates were predicted as potential co-targeted therapeutic agents. Conclusions NDRG1, DLD, and CIRBP were identified as biomarkers for PD, thereby opening new avenues for elucidating disease mechanisms, facilitating early diagnosis, and identifying potential therapeutic targets.